2016
DOI: 10.14744/nci.2016.73383
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of nutritional status with anthropometric measurements and MQSGA in geriatric hemodialysis patients

Abstract: OBJECTIVE:Malnutrition is common among hemodialysis patients and is associated with higher rates of morbidity and mortality. The aim of this study was to evaluate nutritional status of geriatric hemodialysis patients.METHODS:Total of 163 hemodialysis patients were initially screened, and 55 patients (28 males, 27 females; mean age: 72.9±8.4 years) met the criteria for inclusion. Patients were divided into 3 groups according to modified quantitative subjective global assessment (MQSGA) scores: Group I (n=22) no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 28 publications
2
7
1
Order By: Relevance
“…A direct and significant relationship was found between age and malnutrition in hemodialysis patients in this study. Many other studies have also reported that older patients tend to be more prone to nutritional deficiency than younger patients (7,11,12,15). These results indicate the necessity of assessment of nutritional status in older patients.…”
Section: Discussionmentioning
confidence: 72%
See 4 more Smart Citations
“…A direct and significant relationship was found between age and malnutrition in hemodialysis patients in this study. Many other studies have also reported that older patients tend to be more prone to nutritional deficiency than younger patients (7,11,12,15). These results indicate the necessity of assessment of nutritional status in older patients.…”
Section: Discussionmentioning
confidence: 72%
“…Another study carried out in Jordan (19) reported a significantly higher prevalence of malnutrition in women than men. These studies show the necessity of assessment of nutritional status in women undergoing hemodialysis, however Yigit et al in Turkey (7) found no relationship between gender and malnutrition in hemodialysis patients.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations